Comparative assessment of the organization of the colors of the Vita Classical color pallet by digital images and visual analysis for dental bleaching - Oliveira-Junior, O. B. [UNESP]; Cioffi, M. S. [UNESP]; Cesnik, R. M. [UNESP]; Florez, F. L. E. [UNESP]; Bagnato, V. S.; Correa-dos-Santos, D. R.; Fornazari, F. P. (Spie - Int Soc Optical Engineering, 2009)
New formularizations, techniques and devices have become the dental whitening most safe and with better results. Although this, the verification of the levels whitening is being continued for visual comparison, that is an empirical, subjective method, subject to errors and dependent of the individual interpretation. Normally the result of the whitening is express for the amplitude of displacement between the initial and the final color, being take like reference the tonalities of a scale of color commanded of darkest for more clearly. Although to be the most used scale, the ordinance of the Vita Classical (R) - Vita, according to recommendations of the manufacturer, reveals inadequate for the evaluation of the whitening. From digital images and of algorithm OER (ordinance of the reference scale), especially developed for the ScanWhite (C), the ordinance of the tonalities of the scale Vita Classical (R) was made. For such, the values of the canals of color R, G, and B of medium part average of the crowns was adopted as reference for evaluation. The images had been taken with the camera Sony Cybershoot DSC F828. The results of the computational ordinance had been compared with the sequence proposal for the manufacturer and with the earned one for the visual evaluation, carried through by 10 volunteers, under standardized conditions of illumination. It statistics analyzes demonstrated significant differences between the ordinances.